Beyond affiliate status : extrapolating the participation of National Human Rights Institutions in the workings of the African Commission on Human and Peoples' Rights - Ooloka-Onyango, J. (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.